Male Circumcision Pilot Program in Lilongwe, Malawi - Jung, Jaehyun (Consilience, 2012)
Male circumcision is one method of effective prevention against HIV/AIDS. In Malawi, however, male circumcision is not the predominant practice. Project Malawi conducted a pilot program of male circumcision for villagers with fully subsidized operation costs. After we conducted sensitization programs to create demand for circumcision, the rate of male circumcision has increased. This pilot project allowed us to consider the acceptability of male circumcision in Malawi. Unsafe surgery, a long recovery period, religious beliefs, and age were the most-cited reasons Malawians rejected male circumcision. We also have found three critical barriers—operation cost, transportation cost, and opportunity cost—which can largely explain the limited accessibility of male circumcision procedures. Lastly, in order to scale up male circumcision in Malawi, the importance of delivering the complete information and significant availability issues need to be addressed.